2007
DOI: 10.1172/jci30525
|View full text |Cite
|
Sign up to set email alerts
|

A distal single nucleotide polymorphism alters long-range regulation of the PU.1 gene in acute myeloid leukemia

Abstract: Targeted disruption of a highly conserved distal enhancer reduces expression of the PU.1 transcription factor by 80% and leads to acute myeloid leukemia (AML) with frequent cytogenetic aberrations in mice. Here we identify a SNP within this element in humans that is more frequent in AML with a complex karyotype, leads to decreased enhancer activity, and reduces PU.1 expression in myeloid progenitors in a developmentdependent manner. This SNP inhibits binding of the chromatin-remodeling transcriptional regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 52 publications
(60 reference statements)
3
95
0
Order By: Relevance
“…Identification of target genes for such variations is possible by studying the correlation of the genotype and expression of nearby genes, whereas effects of trans-acting variants are more difficult to discover. Recently, regulatory SNPs in nongenic regions underlying complex human diseases have been identified (18,19). The well-established role of MYC in colorectal neoplasia makes it the most promising candidate gene at 8q24.21.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of target genes for such variations is possible by studying the correlation of the genotype and expression of nearby genes, whereas effects of trans-acting variants are more difficult to discover. Recently, regulatory SNPs in nongenic regions underlying complex human diseases have been identified (18,19). The well-established role of MYC in colorectal neoplasia makes it the most promising candidate gene at 8q24.21.…”
Section: Discussionmentioning
confidence: 99%
“…SATB1 binds to special AT-rich sequences and its expression appears to be a positive regulator of PU.1 expression requiring an intact URE. 83 Mice deleted of the Satb1 gene showed lower levels of PU.1 in progenitor cells but not in the terminally differentiated progeny indicating that Satb1 may cooperate in early stages of myeloid development. 83 Satb1 À/À mice, unlike URE À/À mutants, do not develop myeloid leukemia.…”
Section: Gata-1 and Pu1 Levels Are Determinants Of Leukemogenesismentioning
confidence: 99%
“…83 Mice deleted of the Satb1 gene showed lower levels of PU.1 in progenitor cells but not in the terminally differentiated progeny indicating that Satb1 may cooperate in early stages of myeloid development. 83 Satb1 À/À mice, unlike URE À/À mutants, do not develop myeloid leukemia. However, it should be noted that Satb1 À/À mice die prematurely (early postnatal) and the limited life-span may not be sufficient for any myeloid leukemias to develop.…”
Section: Gata-1 and Pu1 Levels Are Determinants Of Leukemogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has recently been shown that a distal single nucleotide polymorphism alters long-range regulation of PU.1 gene in acute myeloid leukemia through modulation of binding of the chromatin-remodeling transcriptional regulator SATB1 (76). As interindividual variation in CCL2 expression and its role in disease pathogenesis are well recognized (8,77,78), we analyzed the ECRs identified in this study for presence of single nucleotide polymorphisms.…”
Section: Discussionmentioning
confidence: 99%